Legal Protection of Prisoners' Right to Health Care Under Law Number 22 of 2022 on Corrections: Normative Analysis and Implementation Challenges - Chintia Permatasari; Noenik Soekorini; Vieta Imelda Cornelis (International Journal of Law and Society, 2026)
The right to health is a fundamental human right that remains inherent to prisoners. This study aims to examine the legal protection of prisoners' right to health care as regulated in Law Number 22 of 2022 on Corrections, as well as its implementation in correctional institutions. The research uses a normative juridical method with statutory and conceptual approaches. The findings show that Law Number 22 of 2022 formally guarantees prisoners' access to health services, including mental health care and special protection for vulnerable groups such as women, the elderly, and persons with disabilities. Key provisions in Articles 10, 11, 12, and 14 establish the state's obligation to provide adequate health services equivalent to community standards. However, in practice, the realization of this right faces several obstacles including: (1) overcapacity of correctional facilities exceeding 180% of ideal capacity, (2) limited medical personnel with many institutions lacking permanent doctors, (3) inadequate health facilities and medicine supplies, (4) complicated referral procedures causing delays in emergency treatment, and (5) insufficient budget allocation. Strengthening technical regulations, improving infrastructure, enhancing cross-sectoral collaboration, and implementing effective oversight mechanisms are essential to ensure effective protection of prisoners' health rights as mandated by the constitution and international human rights standards.